PENGARUH LINGKUNGAN KERJA, SELF-EFFICACY, DAN KARAKTERISTIK PESERTA PELATIHAN TERHADAP TRANSFER PELATIHAN KARYAWAN - YUPITER GULO; NURTI WIDAYATI (Media Bisnis, 2020)
The purpose of this study was to determine the effect of the work environment, self-efficacy, and characteristics of trainees on the transfer of training. Research conducted on the employees of PT. PJB UP MuaraTawar, a subsidiary of PLN, by taking 90 employees as research samples using purposive sampling technique. To analyze data collected using Multiple Linear Regression to prove the research hypothesis. Based on the studies conducted, the results of the analysis show that the work environment, self-efficacy, and characteristics of trainees significantly influence the direction of the training transfer. For this reason, it is suggested that the company pay attention to the work environment, self-efficacy, and characteristics of employee training participants. With the intention of employees can transfer training well and do what has been learned at the training site into work every day.